The Bahá'í Faith (Part One): Origins and the Báb - Holm,Filip (2020)
Part one of an academically-minded yet accessible video essay on the Babi and Baha'i Faiths as a work of public scholarship by a religious studies scholar who is part of the popular 'Religious Studies YouTube' community.
Transcript prepared by Doug Couper from video online at youtube.com/watch?v=bc7AvTq1FGY. See also The Baha'i Faith (Part Two): Baha'u'llah and His Teachings
Keywords: 19th century